The Use of Global English Pare Platform as A Mobile Learning Resource to Learn English Vocabulary - Devi Cahyani; Lalu Jaswadi Putera; Ni Wayan Mira Susanti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
The use of Instagram nowadays has been widely expanded as a source to learn English by the huge number of EFL students. The most popular use of Instagram these days is to learn vocabulary. The account facilitated the English learners the materials for learning. The object of the study was to investigate the Students Perception upon the Use of English Learning Account on Instagram which in this case of study was the account of Global English Pare as a Mobile Learning Resource to Learn English Vocabulary, employed using a descriptive qualitative method with online questionnaire, interview, and documentation as the instruments. The data were collected from second semester English students of E2D class at University of Mataram. The participants in this study were chosen using the cluster sampling technique which resulted in selecting 30 members of English second semester students of University of Mataram. It can be inferred that the student's perception towards Global English Pare account was varied and they dominantly presented positive opinions about the platform which indicated the good reflection upon their experience of using the platform as media to learn vocabulary. The majority of students found the account was very effective to develop their vocabulary mastery by portraying several personal positive reasons recorded in the interview section. Meanwhile, it was also found by the students the few numbers of difficulties during their activities using the platform.